Mental Health Promotion: Stop Self-Diagnosing Through Social Media - Gobel, Sry Ade Muhtya; Elnovani Lusiana; Susanne Dida (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: Mental health is increasingly being recognized as a severe problem. While there has been an increasing awareness of mental health and psychological well-being for economic and social development over the past two decades, there has not been a corresponding increase in mental health investment. Social media platforms allow healthcare practitioners to take full advantage of the potential of social media. However, this good thing is followed by a bad thing, where more and more information is accessible; people use that information to benchmark that they also have a "mental disorder" while not consulting a professional (psychologist/psychiatrist). Incidents like this are commonly referred to as self-diagnosis. Method: Therefore, this study will discuss the existence of information and promotion through accurate and explicit content related to self-diagnosis, using qualitative research with a case study approach. Results: The results obtained are that this accessibility allows the public to seek information about the symptoms they are experiencing, thereby facilitating early detection of mental health disorders. The power of social media to engage audiences to improve communication and expand the capacity to promote programs, products, and services should be valued in health promotion. Conclusion: Social media platforms, regardless of time or location, allow practically infinite opportunities to interact and communicate with others. This ease of use of on-demand communication may be critical in increasing social connection among people suffering from mental illnesses who have difficulty interacting in person.